SYNTACTIC ANALYSIS OF DIFFERENCES OF OPINION IN THE INTENTION OF RAMADAN FASTING - Dede Rizal Munir; Abdurrahman Saleh, (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This research is based on the difference in the intention of fasting in Ramadan, some say Ramadan, some say Ramadan. In this context, the study aims to understand the syntactic structure of the intention of fasting expressed in Arabic. The analysis method used is a descriptive-analytical approach, using basic concepts in Arabic syntax. The data was analyzed in depth to identify the syntactic components involved in fasting intention sentences. The results of the study show that the intention of fasting in Ramadan follows the typical syntactic structure of the Arabic language, with clear subjects, predicates, and objects. In addition, the analysis also revealed the use of keywords that reinforce the purpose and scope of the fast. This study provides a deeper understanding of the syntactic structure of Ramadan fasting intentions, as well as its implications in religious contexts. This research can be the basis for further study of Arabic syntax in religious contexts and can also contribute to the development of further syntactic analysis methods.